Sistem Penstabil Tegangan dalam Manajemen Generator Set - Ratna Aprilia, Dwi; Nuril Achadiyah, Ana; Okiandri, Diki (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2020)
The distribution of electrical energy from the power plant is not always available all the time. This is due to disturbances that occur in the power plant, transmission line and distribution channel. So that consumers who need electrical energy guarantees always need a backup source of electrical energy, in this case a generator set that has sufficient capacity to bear all the required loads. However, the generator set as backup energy will cause the voltage to become unstable. To find out how stable the reserve energy voltage is, a voltage stabilizer system is needed. This research produces a Voltage Stabilizer using a frequency sensor. The voltage stabilizer uses the ZMPT101B voltage sensor. When the main supply (PLN) is interrupted or disconnected, this sensor will give a signal to Arduino, and Arduino will command the Generator set to start. This change is also controlled using an Automatic Transfer Switch (ATS) and can be observed from the frequency value monitored by Delphy and results in an acquired frequency of 0.08 Hz and is able to detect changes in frequency of less than 1 Hz.